Effect of Pre-cooling Combined with Exogenous Oxalic Acid Application on Storage Quality of Mango (Mangifera indica) - Wijewardane , R M N A (Journal of Postharvest Technology, 2014)
This study was undertaken to determine low cost treatments that may be readily adoptable by local producers and exporters to extend the storage life of mango. The experiment was conducted for the var. ‘Karuthacolomban’. The fruits were harvested 13 weeks after flowering. Just after harvesting, the half of the lots of selected fruits were subjected to pre-cooling by using hydro pre-cooling (water temperature 15ºC) till the fruit temperature reaches to 13-15ºC and remaining was kept without pre-cooling. The pre-cooled and non pre-cooled fruits were dipped in 5% sodium bicarbonate solution for 10 min followed by 6 and 8 ppm oxalic acid solution for 10 min, air-dried and the treated fruits were stored at ambient (28-30ºC, 65-70% RH) and low temperature (13±2ºC, 55-60% RH) conditions. The fruits from each treatment were observed to evaluate the physiological weight loss, fruit firmness, total soluble solids, titratable acidity, pH and rate of respiration. The results revealed that fruits dipped in 5% sodium bicarbonate solution followed by 8 ppm oxalic acid application along with pre-cooling was the most effective for extension of storage life of fresh mango up to 12 and 24 days under ambient (28-30ºC, 65-70% RH) and low temperature storage (13±2ºC, 55-60% RH), respectively. Fruits stored under low temperature exhibited better retention of all physiological and biochemical characteristics than the same treatments during ambient storage.